Nitrogen and oxygen isotopomeric constraints on the sources of nitrous oxide and the role of submarine groundwater discharge in a temperate eutrophic salt‐wedge estuary. Issue 4 (10th December 2020) - Wong, Wei Wen; Lehmann, Moritz F.; Kuhn, Thomas; Frame, Caitlin; Poh, Seng Chee; Cartwright, Ian; Cook, Perran L.M.
Abstract: Estuaries have been identified as sources of nitrous oxide (N2 O) emissions to the atmosphere but questions remain as to which production pathway(s) govern the oversaturation of N2 O observed in most estuaries worldwide. Here, we use a suite of nitrate and N2 O isotopes, as well as the 15 N site preference signatures of N2 O to assess (1) the relative importance of different N2 O production pathways in a eutrophic groundwater‐impacted salt‐wedge estuary and the aquifers underlying the estuary and (2) the influence of groundwater input on the overall N2 O saturation in the estuary. This is one of the few studies to examine the effect of groundwater–surface water interaction on N2 O cycling using N2 O isotopes. The site preference values of N2 O in the deep aquifer below the estuary were distinctive (83‰ ± 25‰) and were much higher than in either surface water (21‰ ± 6‰) or shallow groundwater (44‰ ± 8‰), suggesting the influence of multiple biotic and/or abiotic processes which proceed through multiple cycles, and/or the occurrence of a yet unidentified N2 O production pathway. Isotope endmember considerations revealed that nitrifier‐denitrification was the major N2 O production pathway within the shallow aquifer whereas within the estuarine water column, N2 O saturation was governed by chemodenitrification and discharge of N2 O‐laden submarine groundwater. Our study not only emphasizes the substantial, yet often underappreciated role of submarine groundwater discharge in estuarine N2 O budgets, but also highlights the need to reevaluate the importance of the noncanonical denitrification pathways (i.e., chemodenitrification and nitrifier‐denitrification) in controlling the overall N2 O production from estuarine and groundwater environments.